Efficient Perovskite Hybrid Solar Cells by Highly Electrical Conductive PEDOT:PSS Hole Transport Layer. Issue 3 (3rd December 2015) - Huang, Xu; Wang, Kai; Yi, Chao; Meng, Tianyu; Gong, Xiong
Abstract : PEDOT:PSS doped with PEO (polyethylene oxide) is demonstrated to be an efficient hole extraction layer due to its high electrical conductivity and extremely smooth surface. This material is able to boost the efficiency of planar heterojunction perovskite hybrid solar cells.